ANALYSIS OF THE STATE OF THE ART OF HIGH ENERGY FLUX DISSIPATERS IN ELECTRONIC DEVICES (Jóvenes en la Ciencia, 2015)
The importance of heat sinks in electronic devices will be analyzed in this project, the different types, and the factors that affect the performance of a heat sink, like the geometry, size and number of fins, the speed of the flux, the material the heat sink is made of, the diameter and positions of the channels. To understand the difference between a het sink with a fan and one with microchannels a comparision is made in this project.
Keywords: Array; Array; Array; Array; Array